RANCANG BANGUN SISTEM MONITORING DATA PENIMBANGAN TRUK TEBU BERBASIS WEB MENGGUNAKAN METODE WATERFALL - Muhammad Abduramadani; Wahyudi Harianto (Prodi Teknik Informatika, Fakultas Sains dan Teknologi, 2025)
UD Puma Trans, located in Talok Village, Turen District, Malang Regency, is a sugarcane truck weighing service company that faced constraints in data monitoring due to access limitations restricted to local computers. This hampered administrators and management in performing supervision and making decisions requiring flexible information access. To address this issue, a web-based monitoring system for sugarcane truck weighing data was developed using the Waterfall method, aiming to enhance operational efficiency and facilitate flexible information access. The research results indicate that the web-based monitoring system was successfully implemented, with key features including automatic recording of sugarcane truck weighing data and a flexible dashboard display for monitoring. The use of the Waterfall method yielded a well-structured system with comprehensive documentation at each development stage. The system successfully overcame data access limitations by enabling easy remote monitoring via the web platform. System implementation increased operational efficiency by minimizing data entry errors and accelerating the reporting process. System testing demonstrated high effectiveness in assisting the monitoring and decision-making processes for UD Puma Trans management. Therefore, it can be concluded that the implementation of the web-based sugarcane truck weighing monitoring system using the Waterfall method successfully provided an effective solution to the data monitoring problems at UD Puma Trans. This system not only facilitates flexible information access from various locations but also enhances operational efficiency through automated data recording and reporting. The use of the Waterfall method proved appropriate in producing a structured system tailored to user needs, thereby supporting faster and more accurate decision-making processes